The Effect of Profitability, Company Size, Solvency, and Public Accounting Firm Size to Audit Delay on Mining Companies - Elfrida Nadya Nathasya; Negina Kencono Putri; Yanuar Eko Restianto (Valid: Jurnal Ilmiah, 2021)
The purpose of this research is to know and analyze the effect of determinants such as previous audit opinion, debt default, audit gender, and size of public accounting firm on the acceptance of going concern audit opinion on mining company which listed on Indonesia Stock Exchange in 2017-2018. Population on this research are all mining companies that listed on Indonesia Stock Exchange period 2017-2018. Total of observed data in this research is 76 companies. Sampling is done by using purposive sampling method that chosen by certain criteria. Based on the research and data analysis technique using regression analysis with SPSS Application, it shows that previous audit opinion, audit gender, and size of public accounting firm has no significant effect ongoing concern audit opinion. While debt default has a significant effect on going concern audit opinion. The implication from the result above is the result of the analysis show that the variable which play a significant role and have significant effect according to the hypothesis is debt default. So this variable must absolutely be a consideration for auditor in the decision process of giving going concern audit opinion, because it can show the ability of the company to pay their debt at due date which can affect operational activity of a company. To decrease the chance of accepting non going concern audit opinion, the company can increase their current assets, and also decrease their current liabilities. And then for the variable which don’t play a significant role and have no significant effect if according to the hypothesis are previous audit opinion, audit gender, and size of public accounting firm. Even the effect of those variable were not significant, it also must be a consideration for the auditor in decide the audit opinion for a company, and must be a consideration for the third party in deciding which company they want to invest.